Basis For Career Guidance Program Development: Identification Of Transferable Skills In Generation Z Students - Harum, Akhmad (Universitas Islam Negeri Raden Mas Said Surakarta, 2023)
A transferable skill ensures success in learning and at the workplace. This study aimed to identify the transferable skills of Guidance and Counseling students as a basis for the development of career guidance programs. The method used in this research was descriptive quantitative. The researcher collected data using a transferable skills questionnaire. There were 222 students selected using simple random sampling in this study. The results of this study indicated that students’ overall transferable skills were categorized as high, with skill aspects ranging from moderate to very high. The researcher found no gender difference in overall transferable skills (p>0.05). However, upon analyzing each aspect discovered a difference in social skills between male and female students (p<0.05). This study can be the basis for developing Generation Z’s career guidance programs.